Numerical solutions of thin film flows of non-Newtonian fluids via optimal homotopy asymptotic approach - Qayyum, Mubashir; Faisal, Muhammad; Rezapour, Shahram; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2024)
The objective of this research is to recover new solutions in the lifting and drainage cases of thin film flows involving non-Newtonian fluid models namely Pseudo-Plastic (PP) and Oldroyd 6-Constant (O6C). Both of the considered fluids exhibit numerous uses in industry when coupled with thin film phenomena. Some of the industrial applications include decorative and optical coatings, prevention of metallic corrosion and lithography of various diodes, sensors and detectors. For solution purpose, a modified version of Optimal Homotopy Asymptotic Method (OHAM) is proposed in which Daftardar-Jafari polynomials will replace the classical OHAM polynomials in nonlinear problems and provide better results in terms of accuracy. The paper includes a comprehensive application of modified algorithm in the case of thin film phenomena. To validate the obtained series solutions, the paper employs a rigorous assessment of convergence and validity by computing the residual errors in each scenario. For showing the effectiveness of modified algorithm, numerical comparison of classical and modified OHAMs is also presented in this study. Furthermore, the study conducts an in-depth graphical analysis to assess the impact of fluid parameters on velocity profiles both in lifting and drainage scenarios. The results of this investigation demonstrate that the proposed modification of OHAM ensures better accuracy of solutions than the classical OHAM. Consequently, this method can be effectively utilized for tackling more advanced situations.
Keywords: OHAM; thin film; lifting and drainage; validity and convergence